2016
DOI: 10.1038/ncomms12911
|View full text |Cite
|
Sign up to set email alerts
|

Highly tunable refractive index visible-light metasurface from block copolymer self-assembly

Abstract: The refractive index of natural transparent materials is limited to 2–3 throughout the visible wavelength range. Wider controllability of the refractive index is desired for novel optical applications such as nanoimaging and integrated photonics. We report that metamaterials consisting of period and symmetry-tunable self-assembled nanopatterns can provide a controllable refractive index medium for a broad wavelength range, including the visible region. Our approach exploits the independent control of permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
118
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(120 citation statements)
references
References 57 publications
2
118
0
Order By: Relevance
“…[13][14][15][16] Recently, increasing attention has been paid to explore unique plasmonic properties on stretchable substrates. [17][18][19][20][21][22][23] Representatively, researchers have investigated sensory behaviors using plasmonic nanostructures on flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Recently, increasing attention has been paid to explore unique plasmonic properties on stretchable substrates. [17][18][19][20][21][22][23] Representatively, researchers have investigated sensory behaviors using plasmonic nanostructures on flexible substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The precise inter-distance manipulation of the patterns by inhomogeneous thermal shrinkage was monitored following the refractive index of the resulting metamaterials, essential for an effective enhancement of refractive index. 21 Aksu et al reported the development of high-quality bow tie antennas based on high-resolution nanostencil lithography on a PDMS substrate. The optical responses of the antenna arrays were shown to be tuned by the mechanical stretching of the stretchable substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication process can be enabled with material systems that include PS-b-PMMA, which can exhibit a high-order natural spacing length of 10 nm to 200 nm depending on the annealing process [51]. Two-dimensional periodic and symmetric metasurfaces has previously been demonstrated and reported by Ju Young Kim et al in 2016, where it was successfully demonstrated that a large area assembly of structured plasmonic materials using block copolymer self-assembly method was possible [52]. Moving towards a three-dimensional array can be achieved with multi-layer thin film BCP's [53,54], and would empower the next generation of complex optical metamaterials for various applications.…”
Section: Discussionmentioning
confidence: 99%
“…Electro-chemical water splitting has been considered as a promising eco-friendly process that avoids the emission of greenhouse gases or harmful components (i.e., CO 2 or NO x ) [2,3]. In recent decades, several studies have been performed to replace noble-metal-based electrocatalysts with earth-abundant nonnoble metals and highly active materials such as transition-metal alloys, oxides, carbides, nitrides, and phosphides [4][5][6][7][8][9][10][11][12][13][14][15]. However, various issues need to be addressed to achieve high-efficiency overall water electrolysis.…”
Section: Introductionmentioning
confidence: 99%